Gambaran Sedentary Behavior Mahasiswa Universitas Negeri Padang - Zulnalis, Zulnalis; Rusli, Devi (Lembaga Yasin AlSys, 2024)
College can be a difficult time for many students because during this time they face a lot of pressure and challenges that can cause various threats to the physical, social and emotional. Such times make them more susceptible to stress and health problems due to unhealthy lifestyles, one of which is sedentary behavior. This study aims to determine the description of the sedentary behavior of Padang State University students. This study uses a quantitative method using descriptive statistical analysis. The population in this study were Padang State University students in the 2018-2020 intake with a total of 4,166 people. Sampling in the study used the consecutive sampling technique using the Slovin formula with a 10% error tolerance so that a total of 98 respondents were obtained. This study used the Sedentary behavior questionnaire scale by Rosenberg et al (2010) which was adapted into Indonesian and distributed via gform. Based on the results, the mean was 37.3 and SD 23.5. This means that the sedentary behavior of Padang State University students tends to be high.